In silico and in vitro studies of flavanoid content of Uncaria gambir Roxb stem extract on antidiabetic activity - Fawaid, Ainun; Mahfudh, Nurkhasanah; Utami, Dwi; Mohamed, Farahidah (Universitas Ahmad Dahlan, 2025)
Bajakah Kalalawit (Uncaria gambir Roxb.) is a typical plant of the Dayak tribe of Kalimantan, Indonesia. This study aims to evaluate the antidiabetic potential of Bajakah Kalalawit stem extract through in silico and in vitro approaches. In silico analysis was conducted to identify the interaction of bioactive compounds in 96% ethanol extract of Bajakah Kalalawit stems with the alpha-glucosidase enzyme (PDB ID : 5NN8), which is the main target in the treatment of diabetes. The results of molecular simulations showed that 2 bioactive compounds of the flavonoid group, namely Bikisocoumarin (-8.25 kcal/mol) and Pinostrobin (-5.81 kcal/mol) contained in 96% ethanol extract of Bajakah Kalalawit stems have significant inhibitory potential against the enzyme. Furthermore, in vitro tests were conducted to assess the inhibitory activity against the alpha-glucosidase enzyme and its effect on reducing blood glucose levels. The experimental results showed that 96% ethanol extract of Bajakah Kalalawit stems was able to significantly (ρ < 0.05) inhibit alpha-glucosidase activity (IC50 = 0.296 ± 0.004 μg/mL). This finding indicates that Bajakah Kalalawit has the potential as a source of active antidiabetic ingredients that can be further developed as an alternative therapy for diabetes management.